Comparative analysis of inheritance rights of children with different religions from their heirs according to Islamic law and civil law - Khasanofa, Auliya; Larasati, Silvia (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Social and legal complexities that arise due to religious differences in the family, where the issue of inheritance rights often causes conflict and injustice. This study aims to analyse the comparison of the inheritance rights of children of different religions from their heirs according to Islamic Law and Civil Law in Indonesia. The research method used in this study is a comparative method with a qualitative approach. Data was obtained through literature review, including analysis of legal texts and related literature. The results show that in Islamic Law, religious differences are an obstacle for children to receive inheritance rights, thus requiring alternative solutions such as grants and mandatory wills. In contrast, Civil Law provides a more flexible approach, where all heirs, regardless of religion, have equal rights to inheritance. Through this analysis, this research reveals the importance of understanding and an inclusive approach in the regulation of inheritance rights, and emphasizes the need for mediation and dialogue to reach a fair agreement in families that have members with different religious beliefs. The findings are expected to contribute to the understanding of inheritance law in Indonesia and support harmonization efforts in family relationships.